DESIGN AND CHARACTERIZATION OF CHLORZOXAZONE FLOATING BIOADHESIVE DRUG DELIVERY SYSTEM - Kumar Pal, Manish; Deshmukh, Ganesh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the work is to formulate chlorzoxazone floating bioadhesive tablets which will significantly improve the bioavailability of drugs under the condition of prolonged use of drugs and reduce the total dosage of administered drug and reduce the side effect. Methods: Floating bioadhesive tablet was prepared by direct compression of polymer such as HPMCK4M and Carbopol934p in combination. Result: After analysis of different evaluation parameter and drug release, F9 batch was selected as promising formulation for delivery of chlorzoxazone floating bioadhesive tablets with 92.1% drug release at 12th h. Conclusion: It was observed that the combination of polymers in 22.5% (HPMCK4M) and 12.5% (Carbopol 934p) give the best drug release and sustain the drug release for 12 h. Among the other batches, F9 batch was selected as an optimized batch because the pre- and post-compression parameters results are satisfactory.